Prevalence of SCCmec Types I, II, III, and pvl gene among Methicillin-Resistant Staphylococcus aureus (MRSA) isolated from clinical specimens in Sanglah General Hospital - I Gede Sathya Agastya; Agus Eka Darwinata; Komang Januartha Putra Pinatih; Ni Nengah Dwi Fatmawati (Intisari Sains Medis, 2022)
Background: Methicillin-Resistant Staphylococcus aureus (MRSA) is a big challenge for health services worldwide which causes infections both in healthcare and community. Healthcare-associated MRSA (HA-MRSA) strains are shown to be resistant to beta-lactam antibiotics and several non-beta lactam antibiotics. At the same time, the community-associated MRSA (CA-MRSA) tends to be resistant to beta-lactam antibiotics. MRSA carried staphylococcal cassette chromosome (SCCmec) types I, II, III, IV, and V. SCCmec types I, II, and III were predominantly found in  HA-MRSA strain while SCCmec types IV and V predominantly found in CA-MRSA strains. Furthermore, the panton valentine leukocidine (pvl) gene is commonly found in CA-MRSA strains. Therefore, this study aimed to determine the prevalence of SCCmec types I, II, III, and pvl gene in MRSA isolated from clinical specimens in Sanglah General Hospital. Methods: This study was a cross-sectional descriptive study. MRSA was isolated from clinical specimens (sputum, wounds, tissue, blood, etc.) from January 2020 to July 2021 and identified by the Vitek 2 Compact (Biomerieux, France) at the Clinical Microbiology Laboratory of Sanglah Hospital. Prevalence of SCCmec and pvl gene using PCR. Data were analyzed using Microsoft Excel version 2010 for Windows. Results: Most of the specimens (69.56%) were wound. Seventeen (73.91%) out of 23 MRSA isolates were positive for the SCCmec III and pvl gene, while none was positive for the SCCmec I and SCCmec II. About 19 (82.60%) isolates were resistant to two or more non-beta-lactam antibiotics. Conclusions: The isolates of MRSA in this study were predominantly isolated from wound specimens, with the most prevalent genetic element being SCCmec III. In this study, although most MRSA isolates carried SCCmec III that suggested as HA-MRSA, however, most of the strains harbored the pvl gene. This interesting phenomenon needs to be further elucidated.